UJI DAYA HAMBAT KRIM KULIT APEL MANALAGI (Malus sylvestris Mill) TERHADAP BAKTERI PROPIONIBACTERIUM ACNE PENYEBAB JERAWAT DENGAN METODE DIFUSI SUMURAN - Liana Fajriah; Robby Candra Purnama (Program Studi Analisis Farmasi dan Makanan Universitas Malahayati, 2021)
Manalagi apple (Malus sylvestris Mill) is one type of poor apple that has been widely consumed by the people of Indonesia because it has a sweet, delicious taste, and is easy to obtain. This study aimed to test the effectiveness of the anti-acne cream of Manalagi Apple (Malus sylvestris Mill) peel extract against Propionibacterium acnes bacteria. The extract obtained by maceration using 96% ethanol solvent was made into two formulations of cream concentration, namely 5% and 10% then tested on Propionibacterium acne bacteria using MHA media. The method used is the well diffusion method. Manalagi Apple peel extract was declared to meet the requirements for a good cream preparation. The 5% cream formulation has shown an inhibitory effect on Propionibacterium acne bacteria with an average diameter of 19.72 mm (intermedied), a concentration of 10% with a value of 20.11 mm (sensitive). From the results obtained it can be concluded that the preparation of Manalagi apple peel extract cream (Malus sylvestris Mill) is effective in inhibiting the growth of Propionibacterium acne bacteria. The most effective cream is in cream preparations with an extract concentration of 10%.